GRAIN DISCOLORATION: AN EMERGING THREAT TO RICE CROP IN PAKISTAN - M. Ashfaq1; U. Mubashar; M. S. Haider; M. Ali; A. Ali; M. Sajjad (Journal of Animal and Plant Sciences, 2017)
In Pakistan, on an average 6 million tons of rice is produced each year that is about 30% of the world's paddy rice. Rice grain discoloration disease (a bacterial/fungal disease) is emerging as a major threat in Pakistan that deteriorates grain quality and texture. With abrupt changes in climatic conditions in the country, the disease severity may be minor to major across different ecological zones. Grain discoloration affects the grain morphology (size and shape of the grain) and ultimately significantly lower yield of the crop. Grain discoloration also affects the drying, shelling, milling and processing of the rice due to weight loss. In coming years huge loss is expected in Pakistan due to this disease. With the passage of time the disease is also spreading to the major rice growing countries and resulting in huge loss in yield. The complexity of the disease is very serious threat to the rice worldwide. To cope with this alarming disease we have to devise the strategies to better utilization of genetic resources through advanced molecular breeding approaches. In addition to breeding, precise identification of pathogen and improvement in agronomic practices would also help deal with the problem.
Keywords: Grain discoloration; rice; crop disease; breeding and genetics